Students Mathematic Representation ability on Associated Materials in First Middle School - Saputra Saputra; Irvan Irvan; Zulfi Amri (JMEA : Journal of Mathematics Education and Application, 2022)
The purpose of this study was to determine the level of mathematical expression ability of Level VII SMP Pembangunan Perbaungan students to solve problems related to typesetting materials through the Realistic Education Method (PMR). Mathematical representational competence is a student's ability to communicate ideas that arise from the student's way of thinking and are used to facilitate problem solving. This study focuses on the ability of visual representations, representations of mathematical equations or expressions, and representations of written or written text in solving problems related to specific materials.